Integrating Political Strategy and Marketing: Abraham Sridjaja's 2024 Electoral Victory in DKI Jakarta II - Zairul Karim; Asep Setiawan (SWATANTRA, 2026)
Indonesia's open-list proportional system encourages legislative candidates to cultivate personal support while retaining access to party organisations. This study examines how Abraham Sridjaja coordinated these competing demands in the DKI Jakarta II electoral district during the 2024 legislative election. With a heterogeneous urban population and overseas electorate, the constituency reveals interactions between candidate-centred campaigning and party organisation. Employing a qualitative case-study design, the research draws on in-depth interviews with the candidate and campaign, party, volunteer, community, and academic actors, supplemented by electoral records, campaign documents, media archives, regulations, and literature. Data were condensed, compared, and interpreted through Schröder's distinction between offensive and defensive political strategies and Firmanzah's political-marketing mix. The findings indicate that candidate differentiation, hybrid digital and face-to-face communication, and volunteer expansion broadened reach. Party consolidation, coordination across levels, and sustained relationships with community intermediaries helped preserve support and reinforce credibility. Product, promotion, price, and place translated strategic objectives into a coherent political offer, communication system, trust-building process, and distribution network. These elements formed a feedback system in which public engagement generated communication material, organisational networks extended and interpreted messages, and repeated contact strengthened the candidate's credibility. The study argues that electoral performance in a metropolitan constituency may depend on coordinating candidate credibility, hybrid communication, and organisational capacity rather than privileging one resource. It contributes a process-oriented explanation of how offensive expansion and defensive consolidation can be integrated through political marketing. However, its single-case and retrospective design explains perceived campaign mechanisms rather than establishing causal effects or broad generalisability.